AN ENGLISH LEARNING: RURAL STUDENTS BELIEFS - Mulia, Mulia; Amiruddin, Amiruddin; Manan, Abdul; Khairisman, Khairisman (Universitas Pendidikan Ganesha, 2021)
This study departs from the researcher's experience as a volunteer teacher in a school where students face obstacles in learning English due to a lack of motivation and supporting facilities that impact their English performance. Therefore, the purpose of this study is to analyze beliefs in learning English. This study uses a quantitative method with a survey design using Horwitz's Beliefs About Language Learning Inventory questionnaire as a research instrument. The population in this study found 136 students. The instrument used to collect data is a questionnaire. The technique used to analyze the research data is qualitative and quantitative analysis. The findings show that students support various beliefs about learning English. The most common beliefs held by students are motivation and expectations. Students have reasonable confidence in motivation and hope (72.35%) because they have a better education, and a future career can be achieved through good English skills. It can be said that students have good motivation to learn English because they think it will be helpful for their dream job in the future.